DOI: 10.29007/t4xb
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Social Media Platforms in Construction Education to Increase Student Engagement

Abstract: This study evaluates the integration of Social Media (SM) as an informal pedagogical tool to support STEM, by fostering engagement and increasing interactional competency and collaborative skills. Construction engineering education has been plagued with low engagement levels partially due to its timeworn pedagogical means and ineffective use of technology. SM platforms are convenient, and effective informal educational means that encourage engagement and interactions between peers. Nowadays, construction progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…15 Following the initial high-affinity binding of one GHR molecule to GH via binding site 1, GH recruits and facilitates dimerization with a second GHR molecule via its lower-affinity binding site 2. 16 While GH acts as an effective GHR agonist, a single mutation from glycine to lysine at residue 120 in GH binding site 2 transforms the protein into an antagonist. This mutant also binds to and facilitates GHR dimerization, but does not promote signal transduction.…”
Section: Introductionmentioning
confidence: 99%
“…15 Following the initial high-affinity binding of one GHR molecule to GH via binding site 1, GH recruits and facilitates dimerization with a second GHR molecule via its lower-affinity binding site 2. 16 While GH acts as an effective GHR agonist, a single mutation from glycine to lysine at residue 120 in GH binding site 2 transforms the protein into an antagonist. This mutant also binds to and facilitates GHR dimerization, but does not promote signal transduction.…”
Section: Introductionmentioning
confidence: 99%
“…Studies [30][31][32][33] have shown that social media can have a positive impact on learning outcomes as it provides opportunities for learners to engage in collaborative and interactive learning experiences. For example, social media platforms can be used to facilitate discussions, share resources and information, and support peer-to-peer learning.…”
Section: The Social Media Learning Environmentmentioning
confidence: 99%